2015 International Conference on Electrical and Information Technologies (ICEIT) 2015
DOI: 10.1109/eitech.2015.7162947
|View full text |Cite
|
Sign up to set email alerts
|

A novel taxonomy of MANET attacks

Abstract: The vulnerabilities of Mobile Ad hoc Networks (MANETs) make it subject to a large number of attacks. In order to understand the nature and behavior of such attacks, many classification schemes and taxonomies to MANET attacks have been proposed. This paper proposes a new taxonomy to MANETs attacks. The taxonomy is aimed to provide a consistent means of classifying attacks, as well as allowing previous knowledge to be applied to new attacks and providing a structured way to view such attacks. The taxonomy is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In [5] authors proposed a classification attacks that applied in MANETs and based on six attributes: legitimacy of attacking node(external or internal node), the number of nodes participating as an attacker (singleton or collision attack), MANETs vulnerabilities utilized by the attack, the network resources exploited by the attacking node/s, the targeted victim and compromised security service of attack.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In [5] authors proposed a classification attacks that applied in MANETs and based on six attributes: legitimacy of attacking node(external or internal node), the number of nodes participating as an attacker (singleton or collision attack), MANETs vulnerabilities utilized by the attack, the network resources exploited by the attacking node/s, the targeted victim and compromised security service of attack.…”
Section: Related Workmentioning
confidence: 99%
“…Attack position in the network: we can distinguish two types of attack position, as internal attack that is a part of the network action, or as an external attack that is not a part of the system [5], like sniffing and man in the middle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Taxonomies are widely utilized across disciplines for organizing information in a systematic way and for presenting it efficiently and coherently. Taxonomies have been developed to classify: cognitive skills [9], personality attributes [10], information system artifacts [11], network attacks [12], clustering algorithms [13], intrusion detection systems [14], privacy violations [15], etc.…”
Section: Related Workmentioning
confidence: 99%
“…This last node cannot respect the routing protocol rules by disturbing the routing process by inserting false information in the routing messages, modifying their content's or simply not cooperating by deleting them. Indeed, several studies in the literature have shown that the nodes are exposed to several threats security of routing protocol and in [2] they has established a taxonomy of attacks detected in the MANET. Although cryptographic techniques have been widely used in routing to protect routing information, such an approach may not be practical for real MANETs due to heavy computational loads and the lack of ability to detect attacking nodes [3].…”
Section: Introductionmentioning
confidence: 99%